A influência do governo federal sobre cidades na Amazônia: os casos de Marabá e Medicilândia - CARDOSO, Ana Cláudia Duarte (2011)
Despite the existence of several academic works on the process of socio-economical transformation of towns in the south of Pará, little of this literature offered interpretations which considered the spatial configuration as analysis. This article tries to show the origin and evolution of a town like Marabá, which works as counterpoint to the conception of “rural urbanism” that managed the towns “along the roads”, like Medicilândia and nucleus that constitute the town of Marabá. Finally, one notices the explicit real estate speculation operating in Cidade Nova, the third and more recent urban setting installed in Marabá.